Alcohol misuse and critical care admissions in the Northern Territory. Issue 9 (19th September 2021) - Secombe, Paul; Campbell, Lewis; Brown, Alex; Bailey, Michael; Pilcher, David
Abstract: Background: The Northern Territory (NT) has a long history of heavy alcohol consumption with a correspondingly high attributable morbidity and mortality. Aims: To describe the number of admissions to intensive care associated with alcohol misuse. Methods: This is a prospective case–control study including all admissions to NT intensive care units (ICU) between 1 July 2018 and 30 June 2019. Characteristics and outcomes of patients who had an admission associated with alcohol misuse (a composite measure of acute and/or chronic misuse) were compared to those who did not. Primary outcome was the number of admissions associated with alcohol misuse. Secondary outcomes included measures of resource use (length of stay (LoS), need for mechanical ventilation) and mortality adjusted for illness severity. Results: Over the sampling period there were 1664 admissions. After exclusions, 1471 admissions were analysed, of which 307 (21%) were associated with alcohol misuse. Acute or chronic misuse was associated with 3.7% and 12.1% of admissions respectively, while 5.1% met criteria for both. Admissions associated with alcohol misuse more frequently required ventilation (38.4% vs 20.7%, P < 0.01) and had longer ICU (2.8 vs 2.1 days, P < 0.01) and hospital LoS (9.1 vs 7.1 days, P < 0.01). There was no difference in hospital mortality (7.2% vs 7.7%, P = 0.94), even after adjustment for illness severity, hospital and diagnostic category. Conclusions: Alcohol misuse is associated with a substantial number of critical care admissions and consumes considerable acute care resources. Further policy directed at harm minimisation and epidemiological work at jurisdictional and national level is necessary.